Sex and Type Effect on Weight Carcass Recipes in Meat Broiler - Rawdan Jaafar, Maysoon (The Iraqi Journal of Veterinary Medicine, 1996)
Thirty males and (30) females from each of two commerical broiler strains (Lohmman and Euribred) were weighted abd slaughtrered at 56 days of age. Over all mean live body was (1967 g) for males and (1692 g) for females mean abdominal fat repersented (2.48%) of the total fat for males and (3.32%) for females. The mean total fat of the body was (13.8%) for the males and (15.5%) for the females. There were no significant difference between males in mean total fat of both strains at the 5% level but there were significant differences between females. It was concluded that significant differences were evedente between males and females in the carcass and abdominal fat retio but not between strains.